2020
DOI: 10.31234/osf.io/5vdpz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-compassion buffers the adverse mental health impacts of COVID-19-related threats: Results from a cross-sectional survey at the first peak of Hong Kong’s outbreak

Abstract: COVID-19 has brought tremendous and abrupt threats to various aspects of our daily lives, from school and work to interpersonal relationships. Self-compassion is put forth as a salutogenic perspective on oneself that buffers the adverse mental health impacts of these threats. During the peak of a local outbreak in Hong Kong in Spring 2020, 761 participants completed questionnaires on self-compassion, perceived threats, as well as perceived benefits and psychological distress. Controlling for demographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…A growing body of research (e.g., [12][13][14][15][16][17]) suggested that responding in a self-compassionate way when struggling with negative events related to the COVID-19 pandemic, could have alleviated the stress and potential negative outcomes that these events could trigger (see also [18][19][20]). Responding in a self-compassionate way-or compassionate self-responding-refers to a person's ability to kindly accept oneself or show self-directed kindness while suffering [21].…”
Section: Self-compassionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research (e.g., [12][13][14][15][16][17]) suggested that responding in a self-compassionate way when struggling with negative events related to the COVID-19 pandemic, could have alleviated the stress and potential negative outcomes that these events could trigger (see also [18][19][20]). Responding in a self-compassionate way-or compassionate self-responding-refers to a person's ability to kindly accept oneself or show self-directed kindness while suffering [21].…”
Section: Self-compassionmentioning
confidence: 99%
“…Prior research has demonstrated that self-compassion, comprised of both its positive and negative facets, is associated with less psychopathology (see [25] for a meta-analysis) and with higher emotional well-being (see [26] for a meta-analysis). A few cross-sectional studies have also demonstrated that self-compassion may have helped reduce people's intolerance for uncertainty and fear of COVID-19 [13], buffered adverse mental health impacts of COVID-19-related threats [20], and reduced symptoms of depression, anxiety, and stress during quarantine [12]. Regarding our mental health indicators of interest, self-compassion has been found to be cross-sectionally associated with less negative emotions [27,28], more happiness [29], increased life satisfaction [30], and better sleep quality [11].…”
Section: Self-compassionmentioning
confidence: 99%
“…This idea was supported by a recent meta‐analysis that found a small, positive, significant relationship between self‐compassion and sleep quality (Brown et al, 2021). Further, self‐compassion was shown to consistently buffer psychological distress across multiple countries during the COVID‐19 lockdowns (Gutiérrez‐Hernández et al, 2021; Lau et al, 2020). This point is important as during times of stress, individuals are more susceptible to an underactive self‐soothing system and a hyperactive threat system (Gilbert, 2014).…”
Section: Introductionmentioning
confidence: 99%